A class of singular R0-matrices and extensions to semidefinite linear complementarity problems - Sivakumar, K.C. (Yugoslav Journal of Operations Research; Vol 23 No 2 (2013): Vol. 23 No. 2, 2016)
For A ∈ ℝn×n and q ∈ ℝn, the linear complementarity problem LCP(A